The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ol.2018.8377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspirin on proliferation, invasion and apoptosis of Hep‑2 cells via the PTEN/AKT/NF‑κB/survivin signaling pathway

Abstract: Aspirin may exhibit antitumor activities, as it is able to inhibit cell proliferation. However, the ability of aspirin to inhibit cellular proliferation in Hep-2 cells and its underlying molecular mechanisms have been poorly determined. The aim of the present study was to investigate whether aspirin may induce cell apoptosis in the neoplastic cell line Hep-2. The effects of aspirin on the migratory and invasive abilities of Hep-2 cells were also investigated using Transwell assays. In the present study, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The reduction in quantity of CD19.CAR-T cells displaying significant decreases of both CD4 + and CD8 + CD19.CAR-T cells should be taken into account to this negative effect of NSAIDs on CD19.CAR-T cells. This is might be a consequence of the down-regulation of antiapoptotic Bcl-2 family members like Bcl-xl in CD19.CAR-T cells, thereby triggering the intrinsic mitochondrial apoptosis pathway in order to induce cell death by apoptosis, which is confirmed by our data and previous studies (17,(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 89%
“…The reduction in quantity of CD19.CAR-T cells displaying significant decreases of both CD4 + and CD8 + CD19.CAR-T cells should be taken into account to this negative effect of NSAIDs on CD19.CAR-T cells. This is might be a consequence of the down-regulation of antiapoptotic Bcl-2 family members like Bcl-xl in CD19.CAR-T cells, thereby triggering the intrinsic mitochondrial apoptosis pathway in order to induce cell death by apoptosis, which is confirmed by our data and previous studies (17,(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 89%
“…Aspirin has a profound apoptotic effect on cancer cells via Akt, β-catenin, NF-κB or ER stress. The diverse signals converge at the mitochondria where they are integrated, resulting in anti-apoptotic protein downregulation and/or pro-apoptotic protein upregulation [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Mitochondria are central to the coordination of anti-apoptotic and pro-apoptotic networks, and are strictly controlled by Bax- or Bak-based pore channels.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 41 ), found that PTEN overexpression suppressed the growth of bladder cancer cells and significantly induced apoptosis via the downregulation of Survivin and caspase cascade activation. As previously demonstrated, following treatment with aspirin, Hep-2 cells exhibited a significant upregulation of PTEN and the inhibition of nuclear factor (NF)-κB and Survivin, the downstream targets of the PTEN/protein kinase B (AKT) signaling pathway, suggesting that the anticancer molecular mechanism of aspirin may be associated with the inhibition of tumor invasion and the induction of apoptosis by regulating the activity of the PTEN/AKT/NF-κB/Survivin signaling pathway ( 42 ). The aforementioned findings suggest that there may be an association between Survivin and PTEN.…”
Section: Discussionmentioning
confidence: 99%